Ferruginol Restores SIRT1-PGC-1α-Mediated Mitochondrial Biogenesis and Fatty Acid Oxidation for the Treatment of DOX-Induced Cardiotoxicity - Li, Weili; Cao, Jing; Wang, Xiaoping; Zhang, Yawen; Sun, Qianbin; Jiang, Yanyan; Yao, Junkai; Li, Chun; Wang, Yong; Wang, Wei (Frontiers in Pharmacology, 2021)
Background: Doxorubicin (DOX), a broad-spectrum chemotherapy drug, have life-threatening cardiotoxicity. Therefore, searching cardioprotective drugs for DOX-induced cardiotoxicity (DIC) is urgently needed. Objectives: This study aimed to explore cardioprotective effect and specific mechanism by which Ferruginol (FGL) attenuated DIC in vivo and in vitro. Methods: We evaluated the cardioprotection of FGL and performed high-throughput RNA-Seq on DIC mouse. Whereafter, multiple methods including western blot, RT-qPCR, transmission electron microscope, CO-IP, immunofluorescence and other staining methods, and antagonist of SIRT1 and PGC1α were utilized to confirmed cardioprotection and molecular mechanism of FGL. Results: FGL exerted cardioprotection manifested as enhanced cardiac function and reduced structural damage and apoptosis. The transcriptome and other results revealed that FGL facilitated PGC-1α-mediated mitochondrial biogenesis and fatty acid oxidation (MB&FAO) by increasing expression of PGC-1α, and concurrently promoting the expression of SIRT1 enhancing deacetylase SIRT1 deacetylating and activating PGC-1α. Conclusions: These results documented that FGL exerted cardioprotective effects restoring MB&FAO via SIRT1-PGC-1α axis.